Pergulatan Teologi Salafi dalam Mainstream Keberagamaan Masyarakat Sasak - Faizah Faizah (Ulumuna, 2012)
The Salafi movement has recently spread so widely in Indonesia that it has reached rural communities. In that context, its contact with local beliefs and practices produces a dynamic and creative tension between them. This paper will explore the contact dynamics by photographing wrestle of Salafi’s theological movement and beliefs in the mainstream of theological beliefs of local Sasak society of Lombok. The authors found that local knowledge that expressed through practicing several ceremonies associated with the human life-cycle from moment of human birth to death events considered by the Salafi as unauthentic element of Islam called heretic to which the Salafi has to carry out purification. That potential conflict between the Sasak and Salafis, requiring mutual respect and tolerance among them.